2014
DOI: 10.1088/1748-3182/9/3/036005
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, testing and modeling of a new flexible armor inspired from natural fish scales and osteoderms

Abstract: Crocodiles, armadillo, turtles, fish and many other animal species have evolved flexible armored skins in the form of hard scales or osteoderms, which can be described as hard plates of finite size embedded in softer tissues. The individual hard segments provide protection from predators, while the relative motion of these segments provides the flexibility required for efficient locomotion. In this work, we duplicated these broad concepts in a bio-inspired segmented armor. Hexagonal segments of well-defined si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 17 publications
1
73
1
Order By: Relevance
“…Mechanical characterization typically involved tensile testing (Ikoma et al, 2003;Garrano et al, 2012;Lin et al, 2011;Zhu et al, 2012) or indentation and puncture tests on individual scales (Bruet et al, 2008;Meyers et al, 2012;Zhu et al, 2012) or multiple scales (Zhu et al, 2013). Fish scales have also started to inspire new flexible protective systems (Browning et al, 2013;Chintapalli et al, 2014). Tensile tests on natural teleost fish scales confirmed the scale as a stiff, strong a tough material.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical characterization typically involved tensile testing (Ikoma et al, 2003;Garrano et al, 2012;Lin et al, 2011;Zhu et al, 2012) or indentation and puncture tests on individual scales (Bruet et al, 2008;Meyers et al, 2012;Zhu et al, 2012) or multiple scales (Zhu et al, 2013). Fish scales have also started to inspire new flexible protective systems (Browning et al, 2013;Chintapalli et al, 2014). Tensile tests on natural teleost fish scales confirmed the scale as a stiff, strong a tough material.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of shark skin, the hard dermal denticles forming its epidermis bestow it special surface morphology and features. Moreover, the dermis and the subcutaneous tissue beneath the epidermal layer form the main bulk of the skin's structural organization called the elastic matrix, or compliant surface in a literature 30. Naresh et al 31 investigated the mechanical behaviors and the histological characteristics of shark skin in detail.…”
Section: Shark Skin Structurementioning
confidence: 99%
“…Hydrophilic or hydrophobic behavior can suppress instability growth in the boundary layer by changing the interaction behavior of the flow‐wall interface; thus, drag reduction is achieved. Third, physical and mechanical properties of matrixes, including flexibility 30, stiffness 64, and viscoelasticity 49, can induce the riblet‐structured wall to exhibit different responses to fluid flow, thereby resulting in different drag‐reduction effects.…”
Section: Progress In Research and Applications Of Biomimetic Drag‐rmentioning
confidence: 99%
“…This design showed that overlapping of scales provides flexibility, damage tolerance, and more importantly resistance to puncture. Similarly, armadillo scales have also been used as a source of inspiration for designing flexible armor fabricated using hexagonal glass plates placed on an elastomer substrate [25]. This type of synthetic armors also yielded a good resistance to puncture as well as flexibility.…”
Section: Introductionmentioning
confidence: 99%